2018
DOI: 10.5468/ogs.2018.61.2.253
|View full text |Cite
|
Sign up to set email alerts
|

Serum visfatin levels in non-obese women with polycystic ovary syndrome and matched controls

Abstract: ObjectiveThe purpose of the current study was to compare the circulating levels of visfatin between women with polycystic ovary syndrome (PCOS) and those without PCOS and to assess the correlations between visfatin levels and various parameters.MethodsThis case-control study recruited 74 PCOS patients and 74 age- and body mass index (BMI)-matched controls. Serum visfatin levels were evaluated using the enzyme-linked immunosorbent assay. Women with PCOS were divided into 2 subgroups based on the presence of cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 41 publications
2
21
1
Order By: Relevance
“…Therefore, different from another adipose tissue-secreted hormone, leptin, which has confirmed gender-based difference [25], the actions of visfatin may not be regulated by sex hormones. In fact, numerous studies have reported the relationship between visfatin levels and lipoprotein metabolites in patients with metabolic disorders [2628]. In line with these reports, we also found that serum visfatin levels correlated positively with waist circumference, waist-hip ratio, and TG.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, different from another adipose tissue-secreted hormone, leptin, which has confirmed gender-based difference [25], the actions of visfatin may not be regulated by sex hormones. In fact, numerous studies have reported the relationship between visfatin levels and lipoprotein metabolites in patients with metabolic disorders [2628]. In line with these reports, we also found that serum visfatin levels correlated positively with waist circumference, waist-hip ratio, and TG.…”
Section: Discussionsupporting
confidence: 91%
“…Despite some conflicting results [52], a recent meta-analysis revealed that plasma visfatin is significantly increased in subjects presenting overweight/obesity, IR, metabolic syndrome, and cardiovascular diseases [53]. A positive association between circulating visfatin and BMI has been reported by several authors [26,27,34,51] but not confirmed by others [52]. On the contrary, the role of visfatin in the regulation of female reproductive functions is supported by several evidences.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some of these adipokines have been in vitro demonstrated to be implicated in human ovarian follicle function [20] and modulation of steroidogenesis [14,15,16,17,19,21]. Plasma levels of adiponectin [4], chemerin [22,23], resistin [24,25], visfatin [26,27], omentin [28,29], and apelin [19] seem to vary in women with PCOS, but the literature is poor, and results are often discordant [19,30,31,32,33,34]. Further, adipokines were predominantly assessed in blood samples, while very little is known concerning their variations in follicular fluid (FF) and GCs of women with PCOS [19,35,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…PCOS is a female reproductive endocrine disease closely related to chronic inflammation [28,61]. Here, Tremellen et al proposed the hypothesis of the "gut barrierendotoxemia-inflammation mechanism", which concerned the pathogenesis of PCOS [17].…”
Section: Endotoxemiamentioning
confidence: 99%